The Immediate Effects of Expert and Dyad External Focus Feedback on Drop Landing Biomechanics in Female Athletes: An Instrumented Field Study - Kelly A. Leonard (North American Sports Medicine Institute, 2021)
# Background Anterior Cruciate Ligament (ACL) injury prevention interventions have used trained experts to ensure quality feedback. Dyad (peer) feedback may be a more cost-effective method to deliver feedback to athletes.